Aplikasi Kompos Tandan Kosong Kelapa Sawit (Tkks) terhadap Pertumbuhan Padi (Oryza Sativa L.) dengan Metode Sri Modifikasi - Pardosi, Jorricky; Effendi, Arman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The purpose of this research was to find out the effect compost of oil palm emtybunch and to obtain optimum dose for rice growth (Oryza sativa L.) through modificated SRI method. The experiment was conducted in an experimental field of Faculty of Agriculture, Riau University, in January 2019 until April 2019. The experiment was conducted using completely randomized design (CRD) with 5 treatments of oil palm empty bunches compost; 0 t.ha-1, 10 t.ha-1, 15 t.ha-1, 20 t.ha-1 and 25 t.ha-1and 3 replications using modificated SRI method, where watertable was 10 centimeters below soil surface. The observed parameters were: plant height, ratio of the root canopy, plant growth rate, tillers maximum number.The results obtained in the analysis using duncan new multiple range test (DNMRT) at 5%. The result of this research show that oil palm empty bunches compost at adose of 20 t.ha-1 using modificated SRI method where watertable was 10 cm below soil surface gave best result for plant height, ratio of the root canopy, plant growth rate (PGR),tillers maximum number. Keywords: oil palm empty bunches compost, rice plants, modificated SRI